Compound Action Potential of Isolated Spinal Cord: A Biophysical Analysis to Address Activity of Individual Fibers Following Contusion Injury - I. Rad; K. Khodayari; S. Kouhzaei; H. Mobasheri (Journal of Sciences, Islamic Republic of Iran)
Compound action potential (CAP) of spinal cord represents valuable properties of neural fibers including excitability, rate of myelination and membrane integrity. These properties are measured using amplitude, latency and area under curve of CAPs recorded from spinal cord. Here, the isolated spinal cord was set in a double sucrose gap (DSG) chamber and its response to intracellular stimulation was recorded as a CAP signal. Lateral and Dorsal-ventral mechanical presures were then applied on whole spinal cord (WSC) and spinal cord strips (SCS) of isolated spinal cord to mimic spinal cord injury (SCI). In order to identify a representative pattern of CAP applicable in SCI, the recoded CAPs were evaluated, averaged and fitted using Matlab curve fitting toolbox. The results showed a significant decline in the amplitude and conduction velocity (CV) of CAPs caused by SCI in WSC and SCS preparations. This phenomenon was more significant in less myelinated fibers than highly myelinated motoneurons (MNs) and was identified as a decline in the fitted model level. Differential CAPs of WSC and SCS represented mono and biphasic curves that were fitted to Gaussian model levels of “G4” and “G6”, respectively. However, the CAP of injured WSC and SCS preparations fitted to Gaussian model level three “G3”. Based on the comparative study of WSC and SCS preparations the MN pathways can be traced by recorded CAPs. The current approach can be applied in the identification and evaluation of spinal cord function for experimental and clinical purposes.